2016
DOI: 10.1016/j.jacc.2016.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Early High-Dose Erythropoietin Therapy After Out-of-Hospital Cardiac Arrest

Abstract: In patients resuscitated from an OHCA of presumed cardiac cause, early administration of erythropoietin plus standard therapy did not confer a benefit, and was associated with a higher complication rate. (High Dose of Erythropoietin Analogue After Cardiac Arrest [Epo-ACR-02]; NCT00999583).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 32 publications
0
28
0
3
Order By: Relevance
“…A total of 47 studies were identified after exclusion of duplicate or irrelevant references (Figure 1 ). After detailed evaluation, 3 clinical trials (2 case-controlled studies and 1 randomized controlled study) with a total of 606 patients (276 patients received Epo in conjunction to standard of care compared to 330 patients with standard of care alone) were included in our analysis[ 9 - 11 ]. The characteristics of these trials and mean follow-up periods are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 47 studies were identified after exclusion of duplicate or irrelevant references (Figure 1 ). After detailed evaluation, 3 clinical trials (2 case-controlled studies and 1 randomized controlled study) with a total of 606 patients (276 patients received Epo in conjunction to standard of care compared to 330 patients with standard of care alone) were included in our analysis[ 9 - 11 ]. The characteristics of these trials and mean follow-up periods are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, this did not translate into a significant clinical benefit in patients with either acute myocardial infarction or stroke[ 6 - 8 ]. In the setting of OHCA, there is whole body ischemia and clinical studies have shown conflicting results with 2 studies demonstrating mortality benefit with early Epo administration[ 9 , 10 ] and a recent randomized controlled trial with no significant benefit[ 11 ]. In view of these studies, we aim to perform a meta-analysis to assess for any significant mortality benefit of early Epo administration in patients with OHCA.…”
Section: Introductionmentioning
confidence: 99%
“…New onset hypertension or worsening of existing hypertension is relatively common and is associated with increased plasma volume. 7,170,171,[433][434][435][436][437][438] It should also be mentioned that female hormones (e.g., oral contraception, hormone replacement therapy) can increase blood pressure and cause arterial thrombosis, but because of their higher incidence of venous thrombotic events, they will be discussed in the chapter 3.6.1.…”
Section: Erythropoietin and Its Analoguesmentioning
confidence: 99%
“…The impact of early high-dose erythropoietin was also investigated in patients after OHCA in a single blind randomized trial but neither mortality, neither Cerebral Performance Category (CPC) scale improved after this treatment, only rate of thrombotic complications increased [38].…”
Section: Pharmacologic Strategiesmentioning
confidence: 99%